Barlowite, Cu4FBr(OH)6, a new mineral isotructural with claringbullite: description and crystal structure. (December 2014) - Elliott, Peter; Cooper, Mark A.; Pring, Allan
Abstract: The new mineral species barlowite, ideally Cu4 FBr(OH)6, has been found at the Great Australia mine, Cloncurry, Queensland, Australia. It is the Br and F analogue of claringbullite. Barlowite forms thin blue, platy, hexagonal crystals up to 0.5 mm wide in a cuprite-quartz-goethite matrix associated with gerhardtite and brochantite. Crystals are transparent to translucent with a vitreous lustre. The streak is sky blue. The Mohs hardness is 2 –2 .5. The tenacity is brittle, the fracture is irregular and there is one perfect cleavage on {001}. Density could not be measured; the mineral sinks in the heaviest liquid available, diluted Clerici solution (D &3.8 g/cm3). The density calculated from the empirical formula is 4.21 g/cm 3 . Crystals are readily soluble in cold dilute HCl. The mineral is optically non-pleochroic and uniaxial (–). The following optical constants measured in white light vary slightly suggesting a small variation in the proportions of F, Cl and Br: ω 1.840(4) –1 .845(4) and ε 1.833(4) –1 .840(4). The empirical formula, calculated on the basis of 18 oxygen atoms and H2 O calculated to achieve 8 anions and charge balance, is Cu4.00 F1.11 Br0.95 Cl0.09 (OH)5.85 . Barlowite is hexagonal, space group P63/mmc, a = 6.6786(2), c = 9.2744(3) Å, V = 358.251(19) Å 3, Z = 2. The five strongest lines in the powder X-ray diffraction pattern are [ d(Å )(I)(hkl) ]: 5.790(100)(010); 2.889(40)(020); 2.707(55)(112); 2.452(40)(022); 1.668(30)(220).